Current status of interaction between vet institutions and enterprises - V. I. Blinov; A. I. Satdykov; I. V. Seliverstova (Obrazovanie i Nauka, 2021)
Introduction. The implementation of work-based learning in the process of joint vocational instruction by enterprises and VET (vocational education and training) institutions is the most important focus of the educational policy in developed countries. In the Russian Federation, over the past decade, such kind of partnership has been developing both through spontaneous self-organisation and purposefully in the form of several government projects. VET education policy was focused mainly on implementing the World Skills championship movement in the domestic field. As a result, no fundamental changes in institutional and economic structure were implemented to make apprenticeship training compelling for enterprises. Nevertheless, no full-fledged accumulation of information on the dynamics of the development of various forms of work-based learning was carried out to prevent the decent assessment of the current state of apprenticeship training in the Russian Federation and to conduct a comparative international analysis.The present article aims to determine the current status of interaction between enterprises and VET institutions, fulfil the lack of quantitative information on the topic, and test the hypothesis that under the current institutional conditions the interaction frequency and intensity between enterprises and VET institutions in the Russian Federation lag behind similar international indicators.Methodology and research methods. In the course of the research, the methods of socio-historical analysis, the instruments of theoretical and methodological analysis, hypothesis building, assessment and generalisation methods were applied. The empirical part of the present research was formed by the methods of secondary analysis of the Russian and foreign studies on the development of the VET and its interaction with the labour market. In addition, the method of comparative and retrospective analysis of statistical data from Russian and international studies was employed. Finally, the method of questionnaire survey and the method of content analysis of websites of educational institutions and enterprises were used. The study involved 603 VET institutions from 29 constituent entities of the Russian Federation.Results and scientific novelty. One of the most significant research findings is a systemic description of the current status of the partnership between VET institutions and enterprises in the Russian Federation. Main directions and forms of interaction between VET institutions and enterprises in Russia at the end of the second decade of the XXI century were outlined (curricula development, internship for students, and participation in education results assessment). The prospects for the development of partnership between VET institutions and enterprises and the influencing factors (economic and institutional) were determined. The particular Russian characteristics of the interaction between the VET system and the labour market were identified and described as an inharmonious partnership with the employer’s active articulation of a request for a high-quality human resource without proportionate participation in its instruction. The quantitative assessment of current interaction between enterprises and VET institutions in Russia allowed comparative analysis with the indicators of foreign countries to be conducted. In our country, the authors revealed a lower level of enterprises investments (especially financial ones) in the students’ human capital development.Practical significance. The sociological toolkit and schemes of dynamic and comparative analysis developed in the course of the research can be used in further research on the education system and on the related issues. The research findings can be applied while planning and implementing educational policy measures.